2016
DOI: 10.1016/j.schres.2014.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Redox dysregulation, neuroinflammation, and NMDA receptor hypofunction: A “central hub” in schizophrenia pathophysiology?

Abstract: Accumulating evidence points to altered GABAergic parvalbumin-expressing interneurons and impaired myelin/axonal integrity in schizophrenia. Both findings could be due to abnormal neurodevelopmental trajectories, affecting local neuronal networks and long-range synchrony and leading to cognitive deficits. In this review, we present data from animal models demonstrating that redox dysregulation, neuroinflammation and/or NMDAR hypofunction (as observed in patients) impairs the normal development of both parvalbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
199
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(205 citation statements)
references
References 227 publications
5
199
0
1
Order By: Relevance
“…As discussed above, oxidative stress or redox dysregulation contribute crucially to PVI and myelin impairment in SZ. Moreover, as reviewed in Steullet et al, 125 dysregulation of redox homeostasis is fully reciprocal to neuroinflammation and NMDA-R hypofunction (figure 2). This triad constitutes one central pathophysiological "hub" upon which various genetic and environmental risk factors converge during neurodevelopment, leading to structural and functional connectivity impairments.…”
Section: Outlook For Preventive Developmental Therapiesmentioning
confidence: 96%
See 1 more Smart Citation
“…As discussed above, oxidative stress or redox dysregulation contribute crucially to PVI and myelin impairment in SZ. Moreover, as reviewed in Steullet et al, 125 dysregulation of redox homeostasis is fully reciprocal to neuroinflammation and NMDA-R hypofunction (figure 2). This triad constitutes one central pathophysiological "hub" upon which various genetic and environmental risk factors converge during neurodevelopment, leading to structural and functional connectivity impairments.…”
Section: Outlook For Preventive Developmental Therapiesmentioning
confidence: 96%
“…This triad constitutes one central pathophysiological "hub" upon which various genetic and environmental risk factors converge during neurodevelopment, leading to structural and functional connectivity impairments. Drugs targeting the triadic hub of oxidative stress, neuroinflammation, or NMDA-R hypofunction 125 would be promising candidates to prevent deleterious effects on cortical and hippocampal PVI and oligodendrocytes/myelin. As such treatments (eg, omega-3, sulforaphane, NAC) should be applied in early phases of the illness, they should be devoid of serious side-effects.…”
Section: Outlook For Preventive Developmental Therapiesmentioning
confidence: 99%
“…PCP administration to rats results in reduced rates of oxygen uptake in mitochondria isolated from their brains 100 and a meta-analysis of 44 studies identified a total antioxidant status in serum and plasma as a state marker for first-episode psychosis. 101 For these reasons, molecules that possess antioxidant and anti-inflammatory properties may be useful as potential novel treatments the first stages of schizophrenia (for review see 102 ).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis has been driven by postmortem studies revealing altered interneuron-associated markers in brains of patients [5-12]. Several developmental, pharmacological, and genetic manipulations yield loss of interneuron markers such as expression of the calcium-binding protein parvalbumin (PV) in a distinct subset of neurons [13-26], and all these manipulations yield adult animals with a range of behavioral deficits [27]. These data suggest that early-life disruption can lead to long-lasting changes in PV interneurons, supporting the notion that abnormal interneurons can drive altered excitation/inhibition balance.…”
Section: Introductionmentioning
confidence: 99%